Verification of Laboratory Information System - An Observational Study - Ganesh K Poojari; Maitreyee D S (RGUHS Journal of Allied Health Sciences)
Background Laboratory information system LIS plays a vital role in the patient and data management in hospital settings with a well-established laboratory. If the LIS is interfaced with analyzers and hospital information system it is imperative to verify the LIS interfaced to analyzers to avoid any errors in the data transfer that can lead to improper patient care.AimsObjectives The study aimed to verify the LIS interfaced with analyzers for accuracy of data transfer of different tests performed in the analyzers across different steps in the reporting process. It also aimed to address any of the non-conformities NCs in the accuracy of data transfer by taking corrective and preventive actions after performing root cause analysis.Methods The study was conducted in the Biochemistry laboratory of a tertiary care hospital. Data were collected using a checklist at different phases of laboratory automation. About 128 samples were verified for accuracy of data transfer according to the quality system procedure of the laboratory. Fourteen samples were verified as a follow-up for the corrective action taken.Results The accuracy of data transfer from the two autoanalyzers to the LIS was 99.2. The NC was 0.8.Conclusion The LIS and autoanalyzers demonstrated effective performance in transferring patient results during laboratory upgrades minimizing manual data entry. Regular verification and assessment of the LIS are essential following changes to autoanalyzers LIS software updates the introduction of new tests or laboratory relocations.